Aus der AGMB - Reimann, Iris (GMS Medizin – Bibliothek – Information, 2017)
We inform about the main focus of the executive board of the German MLA (AGMB) 2016/2017 and preview the Annual Meeting of the AGMB 2017 in Vienna. We inform about the AGMB competition “Pioneer projects in medical libraries 2017”, about co-operations, travel cost subsidies for members and the weblog medinfo. The migration of the AGMB website to a new provider was completed successfully for the most part.